Acceleration spikes and attenuation response in the trunk in amateur tennis players during real game actions - Delgado-García, G.; Vanrenterghem, J.; Molina-Molina, A.; Soto-Hermoso, V. M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
Although there are numerous locomotion studies analyzing the degree of attenuation of the acceleration spikes in the lower limbs and the trunk, few of these studies relate to tennis, where a high percentage of injuries occur in these body segments. The aim of this study was to describe the acceleration spikes and the attenuation response along the trunk, in real game actions. For this purpose, accelerometers were placed on the lower trunk, the upper trunk, and the head on a sample of 19 players while playing tennis matches. An average of 530 ± 146 acceleration spikes per match were selected in the upper trunk and a clear attenuation response between the upper trunk and the head was found (acceleration spike magnitude was approximately 25 m/s2 in the upper trunk and approximately 20 m/s2 in the head; p < 0.05; with attenuation percentages above 15%). In all players acceleration spikes of the head were below lower and upper trunk acceleration (p < 0.05 in all repeated measures ANOVAs and effect sizes were above 0.8, or large effect sizes). However, between the lower trunk and upper trunk no clear attenuation was found and although in some players the impact peaks were higher in the lower trunk (p < 0.05) the effect sizes were negligible or medium (Cohen d < 0.5). In other players the upper trunk peaks were higher than the lower trunk peaks (p < 0.05) and in a few players there was no significant difference (p > 0.05). The attenuation in the upper trunk, probably serves as a head protection/stabilization mechanism and more studies are needed to analyze the biomechanics actions underlying this attenuation response.